What has been the impact of the high stakes accountability initiatives on principal and teacher behavior in America? - Schuler, Kristine; Martin, Barbara N. (Advances in Social Sciences Research Journal, 2018)
This paper examined the impact high-stakes accountability and data-driven decision-making has had on administrators and teacher leaders. The researchers utilized instructional leadership and teacher leadership as conceptual frameworks to explore the participants’ perceptions concerning the implementation of national reforms. Selected were four single cases (i.e., individual schools), four principals, as well as 28 teachers to “capture multiple realities” (Creswell, 2009, p. 72) within the data. Through analysis, three themes emerged: 1) Changing Culture; 2) Changing Evidence; and 3) Changing Rigor. These themes provide an understanding of the impact high-stakes accountability has had on public school principals and teachers. Revealed are implications for school districts and leadership/teacher preparatory programs.